The Fiqh Al-Hadith Of Digital Media: The Method Of Hadith Understanding Of The Website Bincangsyariah.com And Its Contribution To The Moderate Islam Discourse - Ria Candra Widayaningsih; Muhammad Irfan Helmy (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
In this modern era, website has been considered as an effective and efficient vehicle to disseminate information, including those related to religious and other issues. Thus, a comprehensive understanding on wisdom is greatly necessary to avoid any interfaith conflict. Bincangsyariah.com is a website providing information related to religious issues in the society. The authors have answered those related to fiqh al-hadith found in bincangsyariah.com and its contributions to Islamic Moderate discourse. This study used a discourse analysis method to show and interpret the relationship between patterns and goals expressed through linguistic elements. The results proved that bincangsyariah.com website has provided discussion relevant to the people’s needs for solutions related to various legal problems occurring in the society. This website did not provide any provocative content to hate and abuse certain ethnicity, religion, race, and inter-group relation (known as SARA/Suku, Agama, Ras, Antar-golongan). Thus, Bincangsyariah.com was included to a website intended to widely spread various Islamic Moderate contents